2015
DOI: 10.1002/mop.29283
|View full text |Cite
|
Sign up to set email alerts
|

Simple dual band‐notched UWB antenna loaded with single U‐shaped resonator

Abstract: A simple dual band‐notched antenna is proposed for ultra‐wideband (UWB) applications. The basic UWB antenna, which consists of a half ring‐shaped patch and a trapezoidal ground, occupies a compact area of 25 × 25 mm2. By introducing a single U‐shaped resonator on the patch, dual band‐notched function is realized without increasing the antenna size. An additional resonance near 3 GHz can be excited by the U‐shaped resonator combined with the half ring‐shaped radiator. And the antenna impedance at 3.5 GHz is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
0
10
1
Order By: Relevance
“…Hence, the compact size antenna can easily be imbedded in small devices and MMICs for modern applications. However, the impedance bandwidth (4.86 to 13.66) / 8.8 GHz of the proposed antenna is greater than the impedance bandwidth of the antennas reported in [16], [17], [19], [20] by 800 MHz, 750 MHz, 1800 MHz and 390 MHz, respectively, and lesser than that of the antenna reported in [18] by 200 MHz.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Hence, the compact size antenna can easily be imbedded in small devices and MMICs for modern applications. However, the impedance bandwidth (4.86 to 13.66) / 8.8 GHz of the proposed antenna is greater than the impedance bandwidth of the antennas reported in [16], [17], [19], [20] by 800 MHz, 750 MHz, 1800 MHz and 390 MHz, respectively, and lesser than that of the antenna reported in [18] by 200 MHz.…”
Section: Discussioncontrasting
confidence: 57%
“…From the comparative overview of the peak gain (dBi) between the proposed antenna and reported antennas, it can be observed that peak gain of the proposed patch antenna is greater than that of antennas reported in [17], [20], equal to that of the antenna in [19] and marginally smaller than that of the antennas reported in [16], [18].…”
Section: Discussionmentioning
confidence: 86%
“…To reject these unwanted narrow bands different method was investigated by inserting filters within the UWB antenna with a rejection characteristic, to eliminate the effect of electromagnetic interference (EMI). Many works concentrated the rejection of more than one band, many designers have been published works including dual-band reject [6][7][8][9][10][11][12][13], triple band reject [14][15][16][17], four band reject [18][19][20][21][22][23][24][25][26]. The researchers used different antenna types configuration and different slots configurations to achieve the desired notch filter for a desired narrow band rejection, the slot configuration was inserted on the radiating elements of the patch, depending on the notch frequency and the calculated length of the slot for each notch filter.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [8] used squared patch with partial ground and slotted conductor packed plane, by inserting on the slotted conductor packed pair of mirror L-shaped slots, and U-shaped slot receiving a rejection of WLAN and WiMAX bands respectively. Different planer antenna shaped have been investigated by using one or more U-shaped slot on the patch to achieve WiMAX and WLAN band rejection [9][10][11]. A compact lamp-shaped antenna was designed and inserted a quarter L-shaped slot on the patch and two quarter L-shaped on the ground in order to eliminate the effect of WiMAX and WLAN respectively [12].…”
Section: Introductionmentioning
confidence: 99%
“…The conventional patch antennas having infinite ground plane have narrow bandwidth, low gain and normally operate at a single frequency corresponding to their dominant mode of excitation 3 . Looking these limitations and possible applications of these antennas in UWB systems, extensive work on UWB antennas has been reported in recent times [4][5][6][7] . Jang and Hwang 4 achieved a circular slot type UWB antenna that displays excellent band rejection characteristics in 5GHz rejection band.…”
Section: Introductionmentioning
confidence: 99%